(3bhGfjf GdLRA GdYedi ef UfGYI GdWHs - (3ehSi Hf ejehf Hf jhSa Hf ESMGb, CHhYeQGf GdbQWHj,J (B601 (3g` s
(3ChdgG (B:s
(3bGd cGfJ NVQI SjOi hYeGOi , MQSgG Gddg , ChUJfi Cf CDda dgG cJGHkG ai bhGfjf GdLRA GdYedi ef CLRGA GdWH Ydi WQjb GdaUhd hGdGNJUGQ , aGeJKdJ CeQgG COGe Gddg fSYOgG s
(3BNQgG (B:s
(3hbO PcQJ LejY eG jMJGL ai gPG GdJMQR ai cJGH GdCOhjI GdeSgdI hEdi gfG HdZ GdZQV GdebUhO , hGdMeO ddg s
(3GdhQb (B12 (3ajgG ZjQ hGVMI GdJUhjQs
(3GfXQg eY GdWH GdbTJGdi Qbe(B"581"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B182 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdhWfjI HeOQjO (B(8/5240) s
Keywords: (3GdWHs